Joies, ornaments i llibres a la catedral de Vic a principis del segel XV (III) : els inventaris de la tresoreria, 1416-1424 - Ginebra i Molins, Rafel (Miscel·lània litúrgica catalana, 2006)
Following the publication of the inventories of the cathedral of Vic, which was started in the previous issues, this article introduces the inventories made between 1416 and 1424. In all, six inventories were taken in 1416, 1417, 1418, 1419, 1421 and 1424, and thanks to their closeness they allow to follow up in much detail the variations of the chattels of the sacristy and treasure chamber of the cathedral of Vic. Therefore, a global survey is done together with a parallel edition that allows to follow very clearly the variations taken place over the successive inventories.